Alexandria’s Paradiplomacy: Leveraging Cultural Heritage and Economic Strategies for Mediterranean Leadership - Idrus Malik, Yusuf; Kwei Haliday Nyingchia (Universitas Muhammadiyah Yogyakarta, 2024)
Alexandria, historically known as a nexus of trade and culture, is emerging as a prominent subnational actor in Mediterranean diplomacy through a process known as paradiplomacy. This article explores the mechanisms by which Alexandria harnesses its cultural heritage, strategic positioning, and economic initiatives to strengthen its global influence. Employing a qualitative descriptive methodology, the study drew on secondary data from academic literature, municipal policy documents, and practical case studies of Alexandria’s international collaborations. The findings indicate that Alexandria successfully integrated cultural diplomacy—exemplified by heritage preservation, city branding, and membership in organizations such as the Union for the Mediterranean—with targeted economic strategies to attract foreign investment and expand port infrastructure. These multifaceted efforts bolster Alexandria’s regional standing as a hub of both cultural exchange and commercial activity. However, challenges persist in balancing heritage conservation with modernization demands, including urban development and the maintenance of sustainable economic growth. Overall, this research underscores that Alexandria’s paradiplomatic endeavors not only elevate its role as a cultural ambassador but also enhance its economic competitiveness. By carefully negotiating between historical preservation and forward-looking economic policies, the city demonstrates that local governments can serve as influential agents on the international stage. The article concludes that Alexandria’s experience provides a compelling model for understanding how culturally rich and strategically located cities can leverage paradiplomacy to achieve comprehensive development and greater global engagement.